Scenario evaluation for the management of household solid waste in small Brazilian municipalities - Deus, Rafael Mattos [UNESP]; Battistelle, Rosane Aparecida Gomes [UNESP]; Silva, Gustavo Henrique Ribeiro [UNESP] (Springer Nature, 2017)
As achieving Brazil’s National Policy on Solid Waste-based goals effectively is not simple, there are alternatives such as intermunicipal cooperation by consortium or privatization. Therefore, this study aimed to evaluate the Greenhouse Gas emissions and energy use of six scenarios in two landfills contexts (private and consortium) for small municipalities (less than 100,000 inhabitants as per Brazilian standards) located in São Paulo, Brazil. Through the technique of scenario building and method of Waste Reduction Model was possible to obtain the total energy, the amount of carbon dioxide equivalent (CO2E) and carbon equivalent (CE) emissions. The best scenario integrates composting and recycling, reducing 72 % for CO2E and CE emissions, and saving about 410 % in energy. The landfill consortium will only take advantage, if the location is the most ideal as far as possible. Small municipalities that do not dispose their waste in landfills compatible with regulatory standards may seek for intermunicipal cooperation and adopt integrated waste-management programmes to reduce their environmental impacts.
Keywords: Composting; Household solid waste; Integrated waste management; Recycling; Small municipalities